2009
DOI: 10.1080/10852350903196274
|View full text |Cite
|
Sign up to set email alerts
|

An Initial Evaluation of a Culturally Adapted Social Problem-Solving and Relational Aggression Prevention Program for Urban African-American Relationally Aggressive Girls

Abstract: Recent research demonstrating that relational aggression is associated with peer relationship difficulties, internalizing and externalizing behaviors, social processing deficits, and possibly later mental health disorders among girls has emphasized the need to address the unique expression of aggression amongst females. Despite these findings, almost all aggression interventions have been directed towards physically aggressive boys. In the current manuscript, authors describe the acceptability and initial effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
86
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(87 citation statements)
references
References 36 publications
(37 reference statements)
1
86
0
Order By: Relevance
“…Despite increased attention to the deleterious effects of relational aggression, few tested prevention or intervention programs exist, to date. Moreover, previous attempts to modify children's relationally aggressive behavior have been school-based (Leff et al, 2009;Ostrov et al, 2009). If future researchers confirm that parents model hostile interpretations of peers during conversations with children, family-based programs can be designed to modify parents' attributions and increase parents' provision of effective strategies for handling peer conflict.…”
Section: Discussionmentioning
confidence: 97%
“…Despite increased attention to the deleterious effects of relational aggression, few tested prevention or intervention programs exist, to date. Moreover, previous attempts to modify children's relationally aggressive behavior have been school-based (Leff et al, 2009;Ostrov et al, 2009). If future researchers confirm that parents model hostile interpretations of peers during conversations with children, family-based programs can be designed to modify parents' attributions and increase parents' provision of effective strategies for handling peer conflict.…”
Section: Discussionmentioning
confidence: 97%
“…Further, interventionists and school-based professionals could benefit from considering enacting change both through cognitive and behavioral pathways. For example, Leff et al (2009) demonstrated that an intervention for relational aggression could be effective through targeting both hostile attribution biases and aggressive behavior. In addition, it may be critical to consider the importance of hostile-intent cognitions in a variety of situations for relational, physical, and comorbid aggressors in order for interventions and prevention efforts to be effective.…”
Section: Discussionmentioning
confidence: 98%
“…Recent research suggests moderate effectiveness for school-based intervention programs targeting relationally and physically aggressive African American girls (Leff et al, 2009).…”
Section: Study Strengths and Future Directionsmentioning
confidence: 99%